Acceptability and Marketability of Sunsejack Peanut Brittle - Lumampao, Leslie Catembung (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study aims to know the acceptability and marketability of using sunflower seeds, sesame seeds, and jackfruit seeds when creating a variant of the food brittle. The peanut brittle was created containing different ratios of sunflower, sesame, and jackfruit seeds to know the acceptability of the different ratios in terms of appearance, aroma, color, taste, and texture. The same system was also used to know about the marketability of the created version of peanut brittle in terms of supply availability, product cost, and consumer demand. The gathered data showed varied results from different samples on the different ratios and their criteria. The data gathered in this research were from MAT-Food Technology students who were officially enrolled at Marikina Polytechnic College during the semester, academic year 2022-2023. There were 30 teenagers, 30 adults and 30 young adults that comprised the group of evaluators, by using the 9-Point Hedonic Rating Scale. On the other hand, 30 TLE Teacher, 30 Food Brittle Maker and 30 Seller represented the other group of evaluators, by using the 5-Point Likert Scale. Their evaluations were then compared to know if there are significant differences between the evaluations of different samples on the three ratios and showed varied results across the three ratios in terms of acceptability and marketability. Lab tests were also conducted to analyze the physicochemical properties of the created SUNSEJACK peanut brittle which showed that they contain carbohydrates, protein, a moisture content of 3.7107%, and a pH of 7.1.